Landscape Biographies : Geographical, Historical and Archaeological Perspectives on the Production and Transmission of Landscapes - Renes, Hans; Kolen, Jan; Hermans, Rita (Amsterdam University Press, 2015)
Landscape Biographies explores the long and complex histories of landscapes from personal and social perspectives. As an essential part of human life-worlds, landscapes have the potential to absorb something of people's lives, works, and thoughts. But landscapes also shape their own life-histories at different timescales, transcending human life-cycles and generating their own temporalities and rhythms. It comes as no surprise, therefore, that the co-scripting of landscapes and people figures prominently in the (auto-)biographical works of writers and attracts the interest of geographers, archaeologists, historians, and anthropologists. This has even resulted in a new genre in landscape research, rapidly gaining in popularity, under the heading of 'landscape biography'. In Landscape Biographies, twenty geographers, archaeologists, historians, and anthropologists investigate the diverse ways in which landscapes and monuments have been constructed, transmitted, and transformed from prehistory up to the present, from Manhattan to Shanghai, from Iceland to Portugal, and from England to Estonia. Among the authors are distinguished scholars like Gísli Pálsson, Cornelius Holtorf, Joshua Pollard, and Mark Gillings. 'this rich book offers a way of creating fresh and engaging narratives of our landscapes' - Graham Fairclough, Bulletin KNOB